Evaluation of antinociceptive activity of acmella uliginosa (sw.) cass. methanolic crude extract in mice - Ong, Hui Ming (2013)
In Malaysia, there are various plants being used as a remedy to overcome many types of pain for centuries. However, the actual mechanisms and compounds of these medicinal plants against nociception are yet to be investigated. The present study examined the potential antinociceptive activity of Acmella uliginosa (Sw.) Cass. methanolic crude extract (MEAU) by using both chemicals and thermal models of nociception in mice. The antinociceptive activity of the extract was investigated using acetic acid-induced abdominal constriction test, formalin-induced paw licking test and hot plate test. Then the possible mechanisms of its antinociception through capsaicin, glutamatergic, opioidergic, dopaminergic, serotoninergic, noradrenergic,adenosinergic, nitric oxide-cGMP-PKC pathways and potassium channels systems were studied. Mice that were pretreated with the extract (100 mg/kg, p.o.) were also subjected to the rota-rod test to evaluate the possible non-specific sedative effects by using Ugo Basile, model 47600. Evaluation of acute and chronic toxicity of MEAU were also carried out to determine its safety in oral consumption. It was demonstrated in the present study that MEAU (p.o.) at doses of 3, 10, 30 and 100 mg/kg produced significant dose-dependent inhibition in acetic acid-induced abdominal constriction test, hot plate test, formalin-, capsaicin- and glutamateinduced paw licking test as compared to control. Furthermore, the antinociception caused by the MEAU (100 mg/kg, p.o.) in the acetic acid-induced abdominal constriction test was significantly attenuated by intraperitoneal (i.p.) treatment of mice with naloxone (opioid receptor antagonist, 5 mg/kg), pindolol (a 5-HT1A/1B receptor antagonist, 1 mg/kg) and WAY100635 (a 5-HT1A receptor antagonist, 0.7 mg/kg). It is also worth to mention that MEAU had greatly reversed its antinociception in α2-noradrenergic system (yohimbine, α2-adrenoreceptor antagonist). At the same time, MEAU was found to inhibit pain in the acetic acidinduced abdominal constriction test through nitric oxide pathway by deactivating the L-arginine-NO-cGMP-PKC pathways as well as potassium channels. In contrast,MEAU neither participate in the attenuation of antinociception in the dopaminergic, adenosinergic nor noradrenergic (prazosin, α1 receptor antagonist) systems. MEAU was not associated with non-specific effects such as muscle relaxation or sedation. In addition, MEAU at the dosage of 300 mg/kg (p.o.) did not cause occurrence of death or abnormal behaviour during the period of observation, Together, these results indicate that the methanolic crude extract of A. uliginosa (Sw.) Cass. produced doserelated antinociception in several models of chemical and thermal pain through mechanisms that involve an interaction with opioid system, serotoninergic system (i.e., through 5-HT1A/1B and 5-HT1A receptors), adrenergic system (i.e., through α2 receptor), nitric oxide-cGMP-PKC pathways and potassium channels.